Hybrid Solar Cells of Pyrite-Based/Poly(3-Hexylthiophene) Core/Shell Nanowires - Retana Betancourt, María Fernanda (2021)
Purpose and Study Method: Iron pyrite (FeS2) is a candidate semiconductor in the development of high efficiency photovoltaic devices. A real commercialization of solar cells leads to fabricate photovoltaic devices of earth-abundant and low-cost materials. The FeS2 shows strong optical and electrical properties for solar energy application. Although the highest efficiency for a pyrite-based hybrid solar cell is 3%. The poor performance of the hybrid solar cells is explained by surface passivation and the presence of isomorphs. Raised strategies involve the coupling with wide-bandgapinorganic semiconductor (ZnO) to form p-n heterojunction while the coupling with conducting polymers (Poly(3-hexylthiophene) can form a donor-acceptor interface increasing optical and electrical properties. Therefore, it is the aim of this work the synthesis of photoactive materials of FeS2, ZnO and the polymeric matrix of poly(3-hexylthiophene) in order to study their optical, structural and morphological behavior for their potential application in hybrid solar cells.